The breakup tour - Wibberley, Emily; Siegemund-Broka, Austin (Berkley Romance, 2024)
"A rising star musician has a second chance at love with an old flame she remembers all too well in this swoony romance from the acclaimed authors of The Roughest Draft. Riley Wynn went from a promising singer-songwriter to a superstar overnight, thanks to her breakup song concept album and its unforgettable lead single. When Riley's ex-husband claims the hit song is about him, she does something she hasn't in ten years and calls Max Harcourt, her college boyfriend and the real inspiration for the song of the summer. Max hasn't spoken to Riley since their relationship ended. He's content with managing the retirement home his family owns, but it's not the life he dreamed of filled with music. When Riley asks him to go public as her songwriting muse, he agrees on one condition: he'll join her in her band on tour. As they perform across the country, Max and Riley start to realize that while they hit some wrong notes in the past, their future could hold incredible things. And their rekindled relationship will either last forever or go down in flames"--